Upper extremity rehabilitation using video games in cerebral palsy: A randomized clinical trial - Avcıl, Eren; Tarakçı, Devrim; Arman, Nilay; Tarakçı, Ela (Springer Heidelberg, 2021)
Introduction The aim of the present study was to compare the effects of neurodevelopmental therapy (NDT)-based upper extremity rehabilitation and video game-based therapy (VGBT) using Nintendo(R)wii and leap motion controller (LMC) games on upper extremity function in patients with cerebral palsy (CP). The 30 patients included in the present study were randomized to two groups: VGBT group (VGBT using Nintendo (R) Wii and LMC games) and control group (NDT-based upper extremity rehabilitation). Both groups trained 3 days a week for 8 weeks. Manual dexterity was evaluated using the "Minnesota Manual Dexterity Test (MMDT)", functional ability using the "Childhood Health Assessment Questionnaire (CHAQ)" and the "Duruoz Hand Index (DEI)" and grip and pinch strengths using a dynamometer. Following treatment, significant changes were found, MMDT, grip and pinch strength, CHAQ, and DHI scores in both groups (p < 0.05); however, VGBT group was statistically superior to group II with respect to changes in MMDT (p < 0.05). VGBT using Nintendo(R)Wii and LMC games had slightly superior effects on manual dexterity in patients with CP while compared with NDT-based upper extremity rehabilitation. Futhermore, the effects of both treatment programs on grip strengths and functional ability were similar beneficial.
Keywords: Video Games; Upper Extremity; Rehabilitation; Cerebral Palsy; Leap Motion; Virtual Reality